2022
DOI: 10.17129/botsci.3004
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical composition and biological activities of the plants of the genus Randia

Abstract: Background: The genus Randia L. (Rubiaceae) is native to Americas and highly distributed in tropical areas. Some Randia species are used in traditional medicine in some countries to treat diverse illnesses/symptoms of kidney, circulatory system, lungs, diabetes, cancer, inflammation, and against the bites/stings of snakes and other poisonous animals. Questions: What are the phytochemical compounds previously identified in Randia? What biological activities do they present? Data description: Twenty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…Literature published in the local language (Tamil) and scientific reports have been basis to compare the results and discuss the data. Taxonomic identification was carried out using the flora and leaves [10][11][12][13][14].…”
Section: Study Areamentioning
confidence: 99%
“…Literature published in the local language (Tamil) and scientific reports have been basis to compare the results and discuss the data. Taxonomic identification was carried out using the flora and leaves [10][11][12][13][14].…”
Section: Study Areamentioning
confidence: 99%
“…Además del brevaje, el fruto en sí también se ha reportado como analgésico, antiinflamatorio, y en menor frecuencia se emplea para padecimientos crónicos, como cáncer y diabetes (Ojeda-Ayala et al 2022). El macerado alcohólico de crucetillo también es utilizado como descongestionador, y también como antihemorrágico y antidiarreico, según las experiencias de los consumidores locales.…”
Section: ¿Para Qué Se Utiliza El Fruto Crucetillo?unclassified
“…aculeata, Randia hebecarpa, Randia ferox, Randia momantha are the most studied species 4 . Excessive ethnobotanical and ethnomedicinal study of root, bark, leaves, fruit and seeds of this genus are reported in literature.…”
mentioning
confidence: 99%
“…It is deciduous shrub with thorns or small tree (height up to 5m. ), which is distributed up to 4000 ft altitude throughout the india 4 . Leaves are oval, wrinkled, shiny & pubescent.…”
mentioning
confidence: 99%
See 1 more Smart Citation